Polska w Unii Europejskiej. Jak uczynić członkostwo sukcesem - Płowiec, Urszula (Poland in the European Union. How to Make Membership Success, 2005)
The motives of Poland's accession to the European Union were numerous (political, economic, cultural) likewise the expectations (especially concerning financial support). The negotiated conditions of membership, although, only partially met them (low agricultural payments, no any reduction of the contribution to the EU budget). The greatest achievement of the whole process of preparing to the membership in the EU, it appears, was the capability of the adjusting Polish legal system to the acquis conmunauiaire, stabilization of this system, as well as the adjustment of Polish companies to the forces of single European market. The fundamental challenges that Poland faces at present are the necessity of a marked and sustainable acceleration of economic growth and the decisive reduction in unemployment. The implementation of those challenges may be easier if Poles better govern the new opportunities and threats. Poland became the EU member being in a final stage of the first wave of economic reforms (liberalization of prices, privatization of bancs and enterprises, convertible currency, floating rate of exchange, restructuring of coal and steel industries). The accession to the EU accelerated the necessity of the implementation the second wave of reforms, more difficult and of larger extent (public finance, judiciary system, education, health services, internal security, public service, administration, creation of entrepreneurial behavior, elimination of corruption). The membership of EU make easier the rational governing of opportunities and threats because-on the one hand - it enforces the reforms of public finance, development of road infrastructure, modernization of agriculture, regional development, protection of the environment and knowledge based economic growth. On the other hand, it is likely to obtain net, growing financial support under such conditions that enforce the better functioning of Polish central and local administration and - to some extent - the society. In order to make use of these chances the complex, long term development programme of the economy and the society should be elaborated and executed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 278-290